2011
DOI: 10.1063/1.3527914
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of europium doped zirconia single crystals fibers grown by laser floating zone

Abstract: Yttria stabilized zirconia single crystal fibers doped with europium ions were developed envisaging optical applications. The laser floating zone technique was used in order to grow millimetric high quality single crystal fibers. The as-grown fibers are completely transparent and inclusion free, exhibiting a cubic structure. Under ultraviolet ͑UV͒ excitation, a broad emission band appears at 551 nm. The europium doped fibers are translucent with a tetragonal structure and exhibit an intense red emission at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Recent efforts to develop new single host white light‐emitting phosphors include oxide, oxyfluoride, nitride, oxynitride, sulfide, and halide hosts . Among several host materials, zirconia oxide has good potentialities to become efficient luminescent media due to its wide band gap with high transparency, refractive index, and low vibrational energy cutoff …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent efforts to develop new single host white light‐emitting phosphors include oxide, oxyfluoride, nitride, oxynitride, sulfide, and halide hosts . Among several host materials, zirconia oxide has good potentialities to become efficient luminescent media due to its wide band gap with high transparency, refractive index, and low vibrational energy cutoff …”
Section: Introductionmentioning
confidence: 99%
“…These phosphors may be promising as warm-white-/yellow-emitting phosphors.J ournal luminescent media due to its wide band gap with high transparency, refractive index, and low vibrational energy cutoff. [37][38][39][40] Herein, the synthesis, structural, and photoluminescence properties of a novel material, ZrO 2 :Dy 3+ -Eu 3+ is reported for the first time, which can act as an excellent singlecomponent warm-white-light phosphor for use in near UV-based white LEDs. Its excitation wavelength at around 350 nm fits well with the characteristic emission of near UV LED chips.…”
mentioning
confidence: 99%
“…The peak at 484 nm is synonymous with the shoulder peak observed by Gao and Song in ZrO 2 at room temperature [47]. Soares et al reported a broad emission band at 551 nm due to stabilized zirconia single crystals [48].…”
Section: Photoluminescencementioning
confidence: 93%
“…Induction of fluorescence in zirconia particles. Several studies have described rare earth doping-induced fluorescence in zirconia powders, [38][39][40][41][42][43] but they dealt with di-and trivalent ions that prevent secondary particle formation in our case (experiments not shown). We therefore studied the method of Zhang et al that describes fluorescence induced by CTAB residues after annealing.…”
mentioning
confidence: 97%